Tobati Enggros Village Tourism Development Model In Community Income Increasing Strategy In Jayapura City - Ratang, Yohanis Rante dan Westim; Rante, Andika (Advances in Social Sciences Research Journal, 2018)
Tobati Village and Enggros Village can only be reached by using sea transportation, because it is located in the middle of Youtefa Bay, while transportation is provided by the community traditionally, and only limited to meeting daily needs, so that if there are tourists who want to visit the area of Youtefa Bay attractions must first contact the local community to prepare the boat. There are several alternative wharves to reach the Youtefa Bay area, namely: Jetty at Hamadi Beach, Muara Sungai Hquiry, Vim Beach, Abe Beach and Tanah Hitam. The purpose of this study are as follows: (1) To find out and analyze the inhibiting factors and supporting factors in improving the tourism of Tobati Enggros Village in Jayapura City. (2). To produce a strategy in developing tourism potential of Tobati Enggros Village in Jayapura City. (3) To produce a tourist model of Tobati Enggros Village in Jayapura City and (4). To find out the income of the people in Tobati Enggros Village in Jayapura City. Data analysis techniques are three analytical tools, namely, qualitative descriptive analysis (liker scale) to quantitative descriptive analysis and SWOT analysis through approaches commonly known as Strength Analysis, Weaknesses, Opportunities and Threats or SWOT Analysis (Strengths, Weakness, Opportunities and Threats). The results showed that the strategy for Tobati Enggros village tourism was a strategy: (1) With special autonomy the government was able to increase the availability of human resources who understand tourism potential and how to develop tourism and can increase the allocation of funds. (3) Technological progress must be able to be utilized to develop tourism governance and the quality of human resources. (4) The development and progress of the tourism sector in Indonesia is able to become an important capital to improve tourism promotion that is still lacking. (5) The strategic location and distance between villages that are increasingly integrated make a great opportunity so that the government is able to allocate funds to improve roads and improve governance. (6) Increasing economic growth can make opportunities to be able to increase competitiveness so that it will be able to increase the quantity and quality of human resources. There are 4 (four) models for the development of Tobati and Enggros tourist villages, namely: the development model of villages (1) cultural tourism, (2) water sports tourism, (3) natural tourism, and (4) historical tourism.